Connection Between the Musical Education of Elementary School Teachers and the Use of Information and Communication Technology During Music Lessons - Blatnik, Mateja; Kopačin, Barbara (Revija za elementarno izobraževanje, 2022)
Some teachers take advantage of information and communication technology (hereinafter: ICT) in their music lessons, as it enables transmission of sound, video, and other data via the Internet. Such technology used during music lessons can serve as an accessory for performing specific music activities. The aim of our study was to find how much ICT is used by music teachers and whether there is a connection between formal music education of primary school teachers (formal music education, choir membership, dance activities) and the use of ICT during music lessons. The results show that the use of ICT during music lessons is similar among teachers with and without music education
Keywords: music school, dance lessons, choir, music lessons, information and communication technology